2021
DOI: 10.1155/2021/6656165
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Model Test System for Reconstruction and Expansion of Existing Shallow Single‐Hole Tunnel into Twin‐Arch Tunnel

Abstract: In this study, we developed a tunnel excavation model test system to investigate the deformation and mechanical response of the surrounding rocks and tunnel structure during the reconstruction and expansion of an existing shallow single-hole tunnel into a twin-arch tunnel. A model test was conducted to study the variation in the ground surface settlement characteristics, surrounding rock pressure, and internal stresses of the supporting structure and midwall during the construction process. The influence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In terms of the reasons for the demolition of a tunnel lining, studies have shown that aging [9,10], corrosion, cracks, and other problems of tunnel lining are the main reasons for the demolition. At the same time, the expansion and reconstruction of the tunnel's structure, safety considerations, environmental protection, and other factors will also promote the demolition of the tunnel lining [11,12]. At present, mechanical demolitions and blasting demolitions are mainly used in the demolition of tunnel linings [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the reasons for the demolition of a tunnel lining, studies have shown that aging [9,10], corrosion, cracks, and other problems of tunnel lining are the main reasons for the demolition. At the same time, the expansion and reconstruction of the tunnel's structure, safety considerations, environmental protection, and other factors will also promote the demolition of the tunnel lining [11,12]. At present, mechanical demolitions and blasting demolitions are mainly used in the demolition of tunnel linings [13][14][15].…”
Section: Introductionmentioning
confidence: 99%